Model predictive control of magnetic levitation system - Lafta E. Jumaa Alkurawy; Khalid G. Mohammed (International Journal of Electrical and Computer Engineering (IJECE), 2020)
In this work, we suggest a technique of controller design that applied to systems based on nonlinear. We inform the sufficient conditions for the stability of closed loop system. The asymptotic stability of equilibrium and the nonlinear controller can be applied to improvement the stability of Magnetic Levitation system(MagLev). The MagLev nonlinear nodel can be obtained by state equation based on Lagrange function and Model Predictive Control has been used for MagLev system.